NYERI FIBROMIALGIA NYERI PATOLOGI ATAU NYERI IDIOPATIK - Jan S. Purba* (NEURONA, 2010)
INTRODUCTION FIBROMYALGIA FM IS A CHRONIC MULTIDIMENSIONAL IDIOPATHIC PAIN SYNDROME DEFINED BY WIDESPREAD MUSCULOSKELETAL PAIN THE FM REFERS TO A COLLECTION OF SYMPTOMS WITH NO CLEAR PATHOLOGIC CAUSE BUT THE SYMPTOMS TOGETHER CONSTITUTE A CLEARLY RECOGNIZABLE AND DISTINCT PATHOLOGIC ENTITY